Student Satisfaction with Hostel Facilities: A Case Study of Njala University, Njala Campus, Sierra Leone - Samuel Maxwell Tom Williams; Augustus Osborne; Camilla Bangura; Jonathan Johnny; Ibrahim A. Bakarr; Alusine Hassan Koroma; Janet Boynah Saidu; Jonathan Aruna Musa; George Mayeh Fefegula (European Scientific Journal, ESJ, 2022)
Aim and Scope: The importance of students' social environments intheir day-to-day lives cannot be overstated. The extent to which students arehappy in their hostel depends on its facilities' availability, adequacy, andfunctionality. A case study of Njala University, Njala campus, was used todetermine the amenities provided and the level of satisfaction the students derived from those amenities. Methods: A cross-sectional research designwas used to conduct the research through a close-ended questionnaire. Thestudy's sample size was 482 students. SPSS version 26.0 was used for the dataanalysis. Result: Most (82.0%) of the respondents were within the age group20-29 years, and more than two-thirds (70.7%) were living in overcrowdedrooms with double the number than the room was designed for.; this isattributed to the common phenomenon of students who get a place sub-lettingto their less fortunate colleagues on a cost-sharing basis. Overcrowding hasimplications of increasing pressure on the available facilities. Students werereasonably satisfied with hostel facilities such as recreational grounds, securitystatus, Library/ICT, waste management, and electricity, but very dissatisfiedwith the drainage system, state of mattresses, toilet facilities, water supply,kitchen, room size, laundry, and lack of firefighting devices. Conclusion :Students are dissatisfied with current facilities as enrollment continues to risefaster than Government intervention the paper suggests that a public-privatepartnership be established to fund the construction of other hostels withupdated designs and amenities.